Resolving soft X-ray photons with a high-rate hybrid pixel detector - Hinger, Viktoria; Barten, Rebecca; Baruffaldi, Filippo; Bergamaschi, Anna; Borghi, Giacomo; Boscardin, Maurizio; Brückner, Martin; Carulla, Maria; Centis Vignali, Matteo; Dinapoli, Roberto; Ebner, Simon; Ficorella, Francesco; et al. (Frontiers in Physics, 2024)
Due to their high frame rates and dynamic range, large area coverage, and high signal-to-noise ratio, hybrid silicon pixel detectors are an established standard for photon science applications at X-ray energies between 2 keV and 20 keV. These properties also make hybrid detectors interesting for experiments with soft X-rays between 200 eV and 2 keV. In this energy range, however, standard hybrid detectors are limited by the quantum efficiency of the sensor and the noise of the readout electronics. These limitations can be overcome by utilizing inverse Low-Gain Avalanche Diode (iLGAD) sensors with an optimized X-ray entrance window. We have developed and characterized a prototype soft X-ray iLGAD sensor bonded to the charge integrating 75 µm pixel JUNGFRAU chip. Cooled to -22°C, the system multiplication factor of the signal generated by an impinging photon is ≥ 11. With this gain, the effective equivalent noise charge of the system is ≤ 5.5 e -r.m.s. at a 5 µs integration time. We show that by cooling the system below -50°C, single photon resolution at 200 eV becomes feasible with a signal-to-noise ratio better than 5.